The epidemiology and aetiology of diarrhoeal disease in infancy in southern Vietnam: a birth cohort study. (June 2015) - Anders, Katherine L.; Thompson, Corinne N.; Thuy, Nguyen Thi Van; Nguyet, Nguyen Minh; Tu, Le Thi Phuong; Dung, Tran Thi Ngoc; Phat, Voong Vinh; Van, Nguyen Thi Hong; Hieu, Nguyen Trong; Tham, Nguyen Thi Hong; Ha, Phan Thi Thanh; Lien, Le Bich; et al.
Highlights: The diarrhoeal disease burden in a large, prospective infant cohort in Vietnam is defined. Minimum incidence of clinic-based diarrhoea in infants: 271/1000 infant-years. Rotavirus was most commonly identified, followed by norovirus and bacterial pathogens. Frequent repeat infections with the same pathogen within 1 year. Inclusion of rotavirus in the immunization schedule for Vietnam is warranted. Summary: Objectives: Previous studies indicate a high burden of diarrhoeal disease in Vietnamese children, however longitudinal community-based data on burden and aetiology are limited. The findings from a large, prospective cohort study of diarrhoeal disease in infants in southern Vietnam are presented herein. Methods: Infants were enrolled at birth in urban Ho Chi Minh City and a semi-rural district in southern Vietnam, and followed for 12 months ( n  = 6706). Diarrhoeal illness episodes were identified through clinic-based passive surveillance, hospital admissions, and self-reports. Results: The minimum incidence of diarrhoeal illness in the first year of life was 271/1000 infant-years of observation for the whole cohort. Rotavirus was the most commonly detected pathogen (50% of positive samples), followed by norovirus (24%), Campylobacter (20%), Salmonella (18%), and Shigella (16%). Repeat infections were identified in 9% of infants infected with rotavirus, norovirus, Shigella, or Campylobacter, and 13% of those with Salmonella infections. Conclusions: The minimum incidence of diarrhoeal disease in infants in both urban and semi-rural settings in southern Vietnam was quantified prospectively. A large proportion of laboratory-diagnosed disease was caused by rotavirus and norovirus. These data highlight the unmet need for a rotavirus vaccine in Vietnam and provide evidence of the previously unrecognized burden of norovirus in infants.